Analisis Morfofonemik Muncul Dan Hilangnya Fonem Pada Novel Si Kabayan Jadi Dukun Karya Moh. Ambri - Sri Wahyu Lestari; Ratnawati Ratnawati (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study was motivated by the decline in the use of Sundanese, especially among young people. Sundanese is rich in new vocabulary generated by the process of affixation. Based on this research background, the objective of this study is to further explore the morphophonemic processes of the Sundanese language in novels. Using a qualitative approach, this study analyzes data in the form of stories from the novel Si Kabayan Jadi Dukun by Moh. Ambri, and analyzes them using four types of morphophonemic processes. A literature review was conducted to collect data. The research method is descriptive and qualitative. The data analysis technique is also descriptive. The instrument used in this study is a data card. Data was collected using the literature review technique. This study produced 369 data points showing that the meaning of words changes based on the affixes that accompany them. In the novel Si Kabayan Jadi Dukun by Moh. Ambri, 185 (48.8%) cases of the morphophonemic process of phoneme emergence were found, while 184 (48.5%) cases of the morphophonemic process of phoneme loss were found. Based on the data obtained, there is a slight difference between the two morphophonemic processes in the novel Si Kabayan Jadi Dukun by Moh. Ambri.